Dolutegravir Impairs Stem Cell-Based 3D Morphogenesis Models in a Manner Dependent on Dose and Timing of Exposure: An Implication for Its Developmental Toxicity. (13th September 2021) - Kirkwood-Johnson, Lauren; Katayama, Nana; Marikawa, Yusuke
Abstract: Dolutegravir (DTG) is an antiretroviral drug of the integrase strand transfer inhibitor (INSTI) class used to treat human immunodeficiency virus infection. It is the recommended first-line regimen for most people, including women of childbearing age. However, some human and animal studies have suggested that DTG causes birth defects, although its developmental toxicity remains controversial. Here, we investigated the adverse effects of DTG using pluripotent stem cell-based in vitro morphogenesis models that have previously been validated as effective tools to assess the developmental toxicity of various chemicals. DTG diminished the growth and axial elongation of the morphogenesis model of mouse pluripotent stem cells at exposures of 2 μM and above in a concentration-dependent manner. Concomitantly, DTG altered the expression profiles of developmental regulator genes involved in embryonic patterning. The adverse effects were observed when the morphogenesis model was exposed to DTG at early stages of development, but not at later stages. The potency and molecular impact of DTG on the morphogenesis model were distinct from other INSTIs. Last, DTG altered the growth and gene expression profiles of the morphogenesis model of human embryonic stem cells at 1 μM and above. These studies demonstrate that DTG impairs morphological and molecular aspects of the in vitro morphogenesis models in a manner dependent on dose and timing of exposure through mechanisms that are unrelated to its action as an INSTI. This finding will be useful for interpreting the conflicting outcomes regarding the developmental toxicity of DTG in human and animal studies.